Student Acceptance of Whatsapp Social Media for Teaching and Learning – Case Study of One of Rural Universities in South Africa - Esan, Omobayo; Esan, Dorcas Oladayo (COMPETITIVE: Journal of Education, 2025)
This study explores the potential of WhatsApp as an effective knowledge-sharing platform in educational settings, focusing on students' perceptions. This study aims to evaluate WhatsApp acceptance through the UTAUT model by showing the contributing variables to the acceptance of WhatsApp in an undergraduate program at Walter Sisulu University, South Africa. This study was an ex post facto study with 120 samples distributed proportionally. The data were collected through a questionnaire that was developed from UTAUT model variables and based on the hypothesis test showed that facilitating conditions, behavioural intention, effort expectancy, performance expectancy, and social influence significantly and positively affected behavioural intention. Facilitating conditions and behavioural intention significantly and positively affected WhatsApp acceptance. Variables that greatly contributed to higher WhatsApp acceptance were facilitating conditions and behavioural intention. Facilitating conditions were strongly affected by the student knowledge and university assistance in assisting students to download the applications. Meanwhile, the behavioural intention was strongly influenced by the level of student’s belief in WhatsApp and students’ eagerness for WhatsApp to be integrated with their studies. Nevertheless, social influence variables and behavioural intention were also strongly affected by students' use the WhatsApp for learning.